Poly(methacrylic acid) modification with 2-oxazolines derivatives of bioactive acids: 1-naphtyl acetic acid - Rincón, América; Soutif, Jean Claude (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
Poly(methacrylic acid) (PMA) has been chemically modified by the reaction of a 2-oxazoline derivative producing a polymeric material bearing both ester and amide groups. The 2-(methylenenaphtalene) 4,4-dimethyl-2-oxazoline and 2-(3-pyridine)-4,4-dimethyl-2-oxazoline heterocyclics have been preparedu sing a-napthyl acetic acid and 3-pyridine-carboxylic acid (nicotinic acid) as model compounds. These acids have biological activity and have been employed as plant growth stimulators. Poly (amide-ester)s can be achieved by ring opening reaction of 2-(methylenenaphtalene) 4,4-dimetil-2-oxazoline. The bioactive agent is linked through a spacer ester-amide group to the polymer backbone. The poly(amide-ester) was insoluble in water and characterized by IR spectroscopy technique and proton magnetic resonance 1HRMN. Thermogravimetric analysis of poly(methacrylic acid) modified with 2-(methylenenaphtalene)4,4-dimethyl-2-oxazoline revealed that volatile material was formed in two steps, similarly to the original PMA. How ever, the first de composition process initiates at lower temperature of about 50°C and a mass percentage loss superior to 50% in comparison to PMA. The second volatilization process occurs with a maximum temperature of 398°C, which is 44°C lower than in PMA.